3D Hole Filling Based on Voxel with Weighted Neighbours Interpolation - Sudaryanto, Aris; Ketut Eddy Purnama, I.; Mulyanto Yuniarno, Eko (International Journal of Engineering and Technology, 2019)
Reconstruction is a very important part of 3D visualization. A common reconstruction method is bin filling. Bin filling produces 3D image based on the 2D image and its position. But bin filling process still left empty voxels. That is the reason we do the 3D Hole Filling Based On Voxel With Weighted Neighbours Interpolation. To estimate the empty voxelâ€™s value, in this research the authors do the hole filling process by weighted neighbours interpolation method. To do the interpolation, the empty voxels should be labeled. Then from each of them, the distance of the surrounding non-empty voxels to the empty one are computed. Then certain radius is used as a threshold. The surrounding voxels within the threshold distance are considered as neighbours. Then the value of the empty voxels is determined by the weighted value of the neighboursâ€™ voxel. The method we propose has a high accuracy, as evidenced by a small error value is 11,24373 (from the scale 0 up to 255)Â Â